Patient-reported burden of dry eye disease in the UK: a cross-sectional web-based survey. Issue 3 (4th March 2021) - Hossain, Parwez; Siffel, Csaba; Joseph, Corey; Meunier, Juliette; Markowitz, Jessica T.; Dana, Reza
Abstract : Objectives: To compare sociodemographics and vision-related quality of life (QoL) of individuals with or without dry eye disease (DED); and to explore the impact of DED symptom severity on visual function, activity limitations and work productivity. Design: Cross-sectional web-based survey. Setting: General UK population. Participants: Adults ≥18 years with (N=1002) or without (N=1003) self-reported DED recruited through email and screened. Main outcome measures: All participants completed the 25-item National Eye Institute Visual Function Questionnaire (NEI VFQ-25), with six additional questions (items A3–A8), and the EuroQol 5 dimensions 5 levels. DED participants also completed Impact of Dry Eye on Everyday Life questionnaire, 5-item Dry Eye Questionnaire and the Standardised Patient Evaluation of Eye Dryness questionnaire along with the Ocular Comfort Index, Work Productivity and Activity Impairment and the Eye Dryness Score (EDS), a Visual Analogue Scale. Results: Baseline demographic and clinical characteristics were similar in participants with versus without DED (mean age, 55.2 vs 55.0 years; 61.8% vs 61.0% women, respectively) based on recruitment targets. Scores were derived from NEI VFQ-25 using the new 28-item revised VFQ (VFQ-28R) scoring. Mean (SD) VFQ-28R scores were lower in participants with versus without DED, indicating worse functioning (activity limitations, 73.3 (12.3) vs 84.4 (12.3); socioemotional functioning, 75.3 (21.5) vs 90.3 (16.2); total score, 71.6 (12.8) vs 83.6 (12.6)). Higher percentages of problems/inability to do activities were observed among those with versus without DED. The impact of DED on visual function was worse for participants with more severe DED symptoms, as assessed by EDS. In addition, a higher EDS was associated with worse symptoms on common DED scales and a worse impact on work productivity. Conclusions: DED symptoms were associated with negative effects on visual function, activities and work productivity, whereas worse DED symptoms had a greater impact on vision-related QoL and work productivity.